Precision in Crisis: A Case Study on the Diagnostic Pitfalls in Acute Aortic Dissection - Rama Ellauzi; Swanson Benjamin; Kim A. Eagle (Annals of Internal Medicine: Clinical Cases)
We report the case of a young man with a history of abdominal aortic aneurysm repair who presented with acute chest pain. An initial work-up included a computed tomography (CT) pulmonary angiogram, which ruled out pulmonary embolism but did not reveal an aortic dissection. Subsequent transthoracic echocardiography and gated CT angiography confirmed an acute Stanford type A aortic dissection. This case highlights the importance of considering aortic dissection in differential diagnoses and the limitations of CT pulmonary angiography in detecting aortic abnormalities.